Development of speech material for an Armenian speech recognition threshold test - Sona Sargsyan; Torsten Rahne (Russian Open Medical Journal)
Introduction — For the Armenian language, no standardized audiometric speech perception test is available. The purpose of this research was to develop, digitally record and evaluate an Armenian multisyllabic speech audiometry test, which can be used to measure speech recognition thresholds in Armenian native speakers. Material and Methods — To create a homogeneous multisyllabic speech corpus, Armenian numerals from 10-100 with 2-4 syllables were selected as general sample and digitally recorded by a female native Armenian speaker. For equalizing the speech recognition threshold between the test items, the speech discrimination function for each numeral was subsequently evaluated by five normal hearing native Armenian listeners in an experimental study. Results — Based on the phonemic structure of the Armenian language, 20 phonemically homogeneous test lists were created. The phoneme distributions of each test list correlated significantly and positively with that of the general sample (all Pearson moment correlation coefficients >0.960; all ps <0.001). Comparison of the phoneme distributions of test lists to that of the Armenian language showed that the test lists represent the language corpus quite well. After adjusting for actual threshold levels, speech discrimination functions are comparable between all numerals used. Conclusion — The developed test lists are a phonetically homogenous representation of the Armenian language and serve as an appropriated base for future clinical measurements of speech recognition threshold in Armenian speaking listeners.